Malignant melanoma metastasis in the ileum – two case reports - Živojinov, Mirjana; Lakić, Tanja; Ilić-Sabo, Jelena; Trivunić Dajko, Sandra; Ivanov, Dejan; Živojinov, Srdjan (Vojnosanitetski pregled, 2021)
Introduction. Malignant melanoma is a tumor that develops from melanocytes, so this type of tumor can occur in any part of body containing the cells. Melanoma is less common than other skin tumors. It is very aggressive type of skin tumor with very early metastases and accounts for 75% of cases of death due to skin tumor. In the initial phase the tumor growth is horizontal. Early detection of changes is very important. Over time, as the tumor gets the vertical growth phase, occurrence of metastases depends on the depth of invasion (Breslow). Malignant melanoma metastasizes to regional lymph nodes, but also in the liver, lung, brain and almost any place that can be populated by the haematogenous route. Case report. We reported two cases of patients who were urgently surgically treated in the Emergency Center of Vojvodina, Serbia, with the clinical signs and symptoms of ileus. In both cases, the ileum resection was performed with terminal ileostomy. Histological analysis was performed and through morphology and immunohistochemical profile, in both cases, the diagnosis was metastatic malignant melanoma in the ileum. Conclusion. In patients with diagnosed malignant melanoma of the skin with symptoms of abdominal pain and/or anemia, application of modern imaging techniques is imperative in order to obtain an early diagnosis of gastrointestinal metastases of this tumor, because the rapid detection and radical resection may contribute to the overall survival of these patients.
Keywords: diagnosis; immunohistochemistry; ileus; melanoma; neoplasm metastasis; surgical procedures, operative; treatment outcome